The Reliability of a Novel Structured Testing Device for Single-breath Lung Carbon Monoxide Uptake: A Randomized Comparison Crossover Study - Shihua Yao; Tuping Fu; Kuiqing Lin; Zhongping Wu; Shubing Chen; Liping Zhong; Beilan Shen; Yanqing Xie; Jiaying An; Xudong Wang; Wenting Liu; Xinxin Yu; et al. (BMC Pulmonary Medicine)
Abstract Background With the development and market launch of several new domestic lung diffusing capacity testing instruments, the clinical reliability of the MeHow MeAir 9000 spirometer, featuring a novel turning valve structure, needs to be validated. Objective To evaluate the clinical reliability of lung diffusing capacity measurements using the MeHow MeAir 9000 spirometer. Methods This study included 166 participants: 30 healthy individuals, 68 with interstitial lung disease (ILD), and 68 with chronic obstructive pulmonary disease (COPD). Using a crossover design, participants underwent lung diffusing capacity tests with both the MeHow MeAir 9000 and Jaeger MasterScreen Diffusion spirometers, following the 2017 ERS/ATS standards. The primary indicator was the diffusing capacity for carbon monoxide (D LCO), with the diffusion capacity of carbon monoxide as a percentage of the predicted value (D LCO %pred) as the main categorical indicator. Secondary indicators included D LCO to alveolar volume ratio (D LCO / V A), alveolar volume (V A), inspired volume (V I), breath-hold time (tBH), fractional concentration of inhaled carbon monoxide (F ICO), fractional concentration of inhaled methane (F ICH4), fractional concentration of carbon monoxide in the alveolar space (F ACO), and fractional concentration of methane in the alveolar space (F ACH4). Consistency analysis was performed on the measurements and the classification of lung diffusing capacity impairment severity from both instruments. Additionally, scatter plots and coefficient of variation (CV%) for inhaled carbon monoxide (CO) and methane (CH4) concentrations were analyzed, along with simulator (Hans Rudolph, Kansas City, MO) test results. Results D LCO ‘s Bland-Altman plot showed 95.0% of data points within the 95% CI, with a CCC of 0.988. In the D LCO %pred classification, the ICCs for the ILD group and the COPD group were 0.940 and 0.975, respectively, while the ICC for the healthy subject group was 0.931. These results indicate good consistency for the primary outcome measures. Secondary indicators had varying CCCs, indicating fair to poor consistency (P < 0.05). Scatter plots and CV% for inhaled CO and CH4 concentrations suggested better stability of MeAir over MasterScreen. Simulator test results showed MeAir had a CO error range of -3.80% to -1.00% and CH4 error range of -0.50–1.00%, while MasterScreen had a CO error range of -2.53–0.00% and CH4 error range of -1.83% to -0.63%, indicating superior CO detection by MasterScreen and better CH4 detection by MeAir. Conclusion The MeHow MeAir 9000 spirometer provides high accuracy measurements of lung diffusing capacity and reliable assessment of the severity of diffusing capacity impairment, making it suitable for clinical use. Clinical trial number Not applicable.